2011
DOI: 10.1093/aob/mcr103
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of physical dormancy and ontogeny of the micropyle–water-gap complex in developing seeds of Geranium carolinianum (Geraniaceae)

Abstract: Acquisition of PY in seeds of G. carolinianum occurs after physiological maturity and is triggered by maturation drying. The micropyle and water gap cannot be considered as two separate entities, and thus it is more appropriate to consider them together as a 'micropyle--water-gap complex'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…15 % in Peltophorum pterocarpum (Mai-Hong et al 2003), 12 % in Gleditsia triacanthos (Geneve 2009), G. aquatica (Geneve 2009), Gymnocladus dioicus (Geneve 2009), Lupinus arboreus (Hyde 1954), Trifolium ambiguum (Hay et al 2010), T. pretense (Hyde 1954) and T. repens (Hyde 1954), 11 % in L. digitatus (Gladstones 1958) and Geranium carolinianum (Gama-Arachchige et al 2011). However, the reason why some seeds develop impermeable coats, while others maturing on the same plant produce permeable seed coats remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 % in Peltophorum pterocarpum (Mai-Hong et al 2003), 12 % in Gleditsia triacanthos (Geneve 2009), G. aquatica (Geneve 2009), Gymnocladus dioicus (Geneve 2009), Lupinus arboreus (Hyde 1954), Trifolium ambiguum (Hay et al 2010), T. pretense (Hyde 1954) and T. repens (Hyde 1954), 11 % in L. digitatus (Gladstones 1958) and Geranium carolinianum (Gama-Arachchige et al 2011). However, the reason why some seeds develop impermeable coats, while others maturing on the same plant produce permeable seed coats remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on seed development have shown that the transition from a permeable to impermeable seed coat coincides with the decline in moisture content during the maturation drying phase of seed development (Jaganathan 2016). Indeed, it has been observed in a few species that the seed coat becomes impermeable only when the moisture content of the seeds falls to a specifi c threshold level (Hyde 1954;Gladstones 1958;Egley 1979;Chinnasamy & Bal 2003;Hay et al 2010;Gama-Arachchige et al 2011;Gresta et al 2011). Th us, the number of seeds with impermeable seed coats produced by plants may vary between sites or within years based on the moisture content reached during maturation drying, which is aff ected by the environmental conditions including temperature and relative humidity.…”
Section: Introductionmentioning
confidence: 99%
“…As well as being a protective barrier between the embryo and the environment, the structural and molecular variations found among different coats deeply influence the Journal of Seed Science, v.40, n.3, p.331-341, 2018 physiology of the seed. Particularly, the variations found in the coat thickness affect germination and dormancy (Coen and Magnani, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The seed coat of Rosa rugosa is lignified and hard, which im-pedes the germination of seeds to some extent [13]. The seed coat can be partially corroded with concentrated hydrochloric acid and sulfuric acid so that the seed husk is thinned, the blockage is removed and the seed coat permeability is increased [14] [15] [16]. Our experiment indicated that concentrated acid treatments not only promoted germination of Rosa rugosa seeds, but also disinfected the surface, which is favorable for aseptic germination.…”
Section: Effect Of Seed Coat On Seed Germinationmentioning
confidence: 99%